2005
DOI: 10.1029/2004jc002311
|View full text |Cite
|
Sign up to set email alerts
|

Slope water, Gulf Stream, and seasonal influences on southern Mid‐Atlantic Bight circulation during the fall‐winter transition

Abstract: [1] Observations from autumn 2000 near the shelfbreak front in the Middle Atlantic Bight are used to describe the transition from stratified summer conditions to well-mixed winter conditions over the shelf. During the observational period, the front differed dramatically from climatological conditions, with buoyant Gulf Stream water found shoreward over the subsurface shelfbreak front. Water mass analysis shows a large number of separate water masses with shelf, slope, and Gulf Stream origins. The coolest shel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…This is not surprising since adding a substantial barotropic component to the velocity field might well alter the convergence/divergence patterns in the bottom boundary layer that are inherent to the theory. Rasmussen et al (2005) showed that Chapman's (2000) frontal trapping theory accurately predicted the grounding depth of the shelfbreak front using the full transport, but their observations came from the MAB where the baroclinic flow dominates and the theory does well even with the full transport (Fig. 12b).…”
Section: B Frontal Grounding Positionmentioning
confidence: 99%
“…This is not surprising since adding a substantial barotropic component to the velocity field might well alter the convergence/divergence patterns in the bottom boundary layer that are inherent to the theory. Rasmussen et al (2005) showed that Chapman's (2000) frontal trapping theory accurately predicted the grounding depth of the shelfbreak front using the full transport, but their observations came from the MAB where the baroclinic flow dominates and the theory does well even with the full transport (Fig. 12b).…”
Section: B Frontal Grounding Positionmentioning
confidence: 99%
“…average of 75 m [Rasmussen et al, 2005]. Although the front meanders up to 50 km horizontally on short time scales, it is usually found within a narrow band (10-20 km), extending hundreds of km, following the shelf break [Loder et al, 1998b;Fratantoni and Pickart, 2007].…”
Section: General Circulation Of the Mid-atlantic Bightmentioning
confidence: 99%
“…The water does not exit the MAB at the shelf break but rather runs along the shelf and exits to the south near Cape Hatteras (Brian 2009). Studies by Rasmussen et al (2005) showed that the cross shelf transport at the shelf-slope edge (shelf break) is small and supports the notion of large along-shelf transport in the MAB. Between 75 and 90 % of the along-shelf sub-inertial current energy can be attributed to wind-forced motions and freely propagating waves (Noble et al 1983).…”
mentioning
confidence: 63%